How Regional Integration and Transnational Energy Networks Have Boosted FDI in Turkey (and May Cease to Do So) : A Case Study--How Geo-Political Alliances and Regional Networks Matter - Sanchez Martin, Miguel Eduardo; Escribano Frances, Gonzalo; de Arce Borda, Rafael (World Bank Group, Washington, DC, 2014)
Turkey has historically struggled to attract foreign investors. This paper argues that not only macroeconomic and political stability, but also regional integration explains the upsurge in foreign direct investment observed since 2005. The analysis draws from a qualitative framework. It discusses how, contrary to the Customs Union Treaty for industrial products with the European Union, the official start of the European Union's accession to negotiations in 2005 encompassed a wide set of reforms in several chapters directly or indirectly affecting the business climate. The reforms helped to enhance foreign direct investment attraction in Turkey. However, it seems that the global economic slowdown starting in 2009 and increasing Euro-skepticism have already started to erode this effect. Only large foreign investment in the energy sector observed in 2009-13, explained by the energy security strategy of the European Union and the privatization agenda, has prevented the collapse of foreign direct investment inflows to Turkey.